Glycated albumin may have a complementary role to glycated hemoglobin in glucose monitoring in childhood acute leukemia - Soo Yeun Sim; Su Jin Park; Jae Won Yoo; Seongkoo Kim; Jae Wook Lee; Nack-Gyun Chung; Bin Cho; Byung-Kyu Suh; Moon Bae Ahn (Korean Society of Pediatric Endocrinology, 2024)
Purpose Glycated hemoglobin (HbA1c) as a glycemic index may have limited value in pediatric patients with acute leukemia as they often present with anemia and/or pancytopenia. To address this issue, we evaluated the usefulness of glycated albumin (GA) as a glycemic monitoring index in pediatric patients with acute leukemia. Methods Medical records of 25 patients with type 2 diabetes mellitus (T2DM), 63 patients with acute leukemia, and 115 healthy children from Seoul St. Mary's Hospital, The Catholic University of Korea, were retrospectively investigated for serum GA, HbA1c, and fasting blood glucose (FBG) levels, along with demographic data. Results GA, HbA1c, and FBG levels did not differ between the control and acute leukemia groups. In the T2DM group, positive correlations were observed among GA, HbA1c, and FBG (P<0.01). Although GA level was not associated with the HbA1c level in the control group, GA and HbA1c levels showed a positive correlation in the acute leukemia group (P=0.045). Regression analysis revealed GA and HbA1c levels to be positively correlated in the acute leukemia and T2DM groups even after adjusting for age, sex, and body mass index z-score (P=0.007, P<0.01). Conclusions GA may be a useful complementary parameter to HbA1c for glycemic monitoring in pediatric patients with acute leukemia, similar to its use in patients with T2DM.